Imagens simbólicas da maternidade a partir de mães youtubers - Schneider, Raquel (2020)
This paper reflects on the symbolic images of motherhood that emerge from the production of moms who have YouTube channels, one of the leading digital social networks of our times. The general objective of the research is to understand wich symbolic images of motherhood manifest themselves in the videos produced by mothers who are youtubers. The concept of symbolic image is situated according to Hans Belting's anthropology of image. From this bias, a history of the symbolic images of motherhood in Brazil from the colonial period to the present day is elaborated, with a focus on evaluating also if there are changes and / or continuities in the images that mothers project on their YouTube channels in relation to to what historically and socially presents itself on this study. The research methodology adopted was Content Analysis (Bardin, 2011), used in the stage of defining the YouTube channels to be evaluated and which also later guided the analysis of the videos of the five channels that make up the study corpus: Babi Sabbag, Flavia Calina, Hel, Macetes de Mãe and Tali Mãe dos Bê. The conclusions of the work point to a rescue of some historical symbolic images (good mother, educating mother and flexible models of motherhood), which are resignified, as well as the emergence of other images from a context marked especially by the presence of screens, which this study proposes to call “performative motherhood” and “tutorial motherhood”.